2015
DOI: 10.1007/s11999-014-4024-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Crosslinking and Vitamin E Stabilization Influence Microbial Adhesions on UHMWPE-based Biomaterials?

Abstract: Our results suggest that VE-PE and XLPE may have an added benefit of being more resistant to bacterial adhesion, even fungal strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 34 publications
3
22
1
Order By: Relevance
“…For example, Banche et al and Gómez-Barrena et al reported that vitamin E-doped or -blended PE had the potential to reduce bacteria adhesion [12][13][14]. However, vitamin E blending has also been shown to reduce bacterial adhesion by only about one-tenth or less [12][13][14][15][16]. Moreover, Williams et al reported that vitamin E-blended PE did not have the ability to reduce biofilm formation [16], which was consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…For example, Banche et al and Gómez-Barrena et al reported that vitamin E-doped or -blended PE had the potential to reduce bacteria adhesion [12][13][14]. However, vitamin E blending has also been shown to reduce bacterial adhesion by only about one-tenth or less [12][13][14][15][16]. Moreover, Williams et al reported that vitamin E-blended PE did not have the ability to reduce biofilm formation [16], which was consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies evaluated bacteria adherence to vitamin E-blended PE [12][13][14][15][16]. For example, Banche et al and Gómez-Barrena et al reported that vitamin E-doped or -blended PE had the potential to reduce bacteria adhesion [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations